Hypertension, an Emerging Problem in Rural Cameroon: Prevalence, Risk Factors, and Control - Walters Tabi Arrey; Christian Akem Dimala; Julius Atashili; Josephine Mbuagbaw; Gottlieb Lobe Monekosso (International Journal of Hypertension)
Background. Despite the increasing trends suggesting that hypertension is a growing public health problem in developing countries, studies on its prevalence, associated risk factors, and extent of blood pressure control have been inequitably done in urban and rural communities in these countries. We therefore aimed to determine the prevalence of hypertension and extent of blood pressure control in rural Cameroon. Methods. This was a community-based cross-sectional study conducted in rural Cameroon (the Moliwe Health Area). Participants aged 21 years and above were recruited by a probability proportional to size multistage sampling method, using systematic sampling for household selection and random sampling for participant selection. Blood pressure, weight, and height were measured by standard methods. Hypertension was defined as BP ≥ 140/90 mmHg. Results. The prevalence of hypertension among the 733 participants recruited was 31.1% (95% CI: 27.8–34.6) and 71% (95% CI: 58.7–81.7) of these hypertensive patients were newly diagnosed. Only 21.2% (95% CI: 12.1–33.3) of known hypertensives had a well controlled BP. Age, obesity, low educational status, and being married were associated with HTN after adjusting for confounders. Conclusions. The high prevalence of hypertension and inadequate BP control among known hypertensives in rural Cameroon warrants greater sensitization and regular screening to reduce hypertension-related morbidity and mortality.